Allelic variation in the DR subregion of the human major histocompatibility complex. - Bell, J I (1987)
Allelic variation in the DR subregion of the human major histocompatibility complex has been analyzed by nucleic acid sequencing of cDNA clones obtained from cell lines homozygous by consanguinity for all the common serological types DR1-9. Two expressed loci were identified in the haplotypes DR2, -3, -4, -7, and -9; one locus being present at a much lower frequency (4-7%) than the other. The low-frequency allele was highly conserved between each of the DRw53 (DR4, -7, -9) and the DRw52 (DR3, -5, -6) haplotypes. Analysis of the variation between alleles confirms the presence of three allelic hypervariable regions. At each variable residue, a limited range of amino acid substitutions are found, distinguishing them from immunoglobulin hypervariable regions. Dinucleotide substitutions are extremely common. Individual hypervariable regions are often shared between haplotypes. Much of the variation in these alleles can be attributed to the shuffling of these regions between haplotypes, possibly by the mechanism of gene conversion.